Smad4 controls signaling robustness and morphogenesis by differentially contributing to the Nodal and BMP pathways - Luca Guglielmi (Nature Portfolio, 2021)
The role of the transcriptional effector SMAD4 in vertebrate embryo development remains unresolved. Here the authors show that in the absence of Smad4, dorsal/ventral embryo patterning is disrupted due to the loss of BMP signaling, while Nodal signaling is maintained, but insufficient for optimal endoderm specification.